Degeneration Process of Fungiform Taste Buds After Severing the Human Chorda Tympani Nerve—Observation by Confocal Laser Scanning Microscopy. Issue 3 (March 2015) - Saito, Takehisa; Ito, Tetsufumi; Ito, Yumi; Kato, Yuji; Manabe, Yasuhiro; Narita, Norihiko
Abstract : Objective: To elucidate the degeneration process of fungiform taste buds after severing the chorda tympani nerve (CTN) by confocal laser scanning microscopy in vivo. Study Design: Prospective study. Setting: University hospital. Patients: Seven consecutive patients whose CTN was severed during tympanoplasty for middle ear cholesteatoma. Intervention: Diagnostic. Main Outcome Measures: Preoperative and postoperative gustatory functions were assessed by electrogustometry (EGM). An average of 10 fungiform papillae (FP) in the midlateral region of the tongue were periodically observed, and the number of taste buds was counted using a confocal laser microscope. Among them, 2 to 3 reference FPs were scelected based on the typical form of the FP or characteristic arrangements of taste pores. Observation was performed before surgery, 1 or 2 days after surgery, 2 or 3 times a week until 2 weeks after surgery, once a week between 2 and 4 weeks, and every 2 to 4 weeks thereafter until all taste buds had disappeared. Results: EGM thresholds showed no response within 1 month after surgery in all patients. The initial change in the degeneration process was the disappearance of taste pores. The surface of taste buds became covered with epithelium. Finally, taste buds themselves atrofied and disappeared. The time course of degeneration differed depending upon individuals, each FP, and each taste bud. By employing the generalized linear mixed model under the Poisson distribution, it was calculated that all taste buds would disappear at around 50 days after surgery. Conclusion: Confocal laser scanning microscopy was useful for clarifying the degeneration process of fungiform taste buds.